2019
DOI: 10.1111/josh.12840
|View full text |Cite
|
Sign up to set email alerts
|

School‐Located Influenza Vaccination: Do Vaccine Clinics at School Raise Vaccination Rates?

Abstract: BACKGROUND: Only half of US schoolchildren receive influenza vaccine. School-located influenza vaccination (SLIV) might raise vaccination rates but conducting flu vaccine clinics at schools is challenging to implement. We compared 2 school-based programs designed to raise influenza vaccination rates: parent reminder/educational messages sent to parents from schools which is a low-intensity intervention vs the combination of reminder/educational messages plus SLIV clinics which is a high-intensity intervention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…With respect to framing strategies in health communication, vaccination inclusion in the school-based program grants the vaccination medical legitimacy, which also influences parental uptake [ 65 ]. These findings are in line with those of other studies showing various reasons for parental preference for vaccinating their children at school, among them lack of access to medical services, limited time to take children for vaccinations, inability to leave work for this purpose and more [ 66 68 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…With respect to framing strategies in health communication, vaccination inclusion in the school-based program grants the vaccination medical legitimacy, which also influences parental uptake [ 65 ]. These findings are in line with those of other studies showing various reasons for parental preference for vaccinating their children at school, among them lack of access to medical services, limited time to take children for vaccinations, inability to leave work for this purpose and more [ 66 68 ].…”
Section: Discussionsupporting
confidence: 91%
“…With respect to the sex of the child in the case of the HPV vaccination, the results of the current study are in line with other studies showing that the child’s gender plays a role in mothers’ decision-making regarding the HPV vaccination [ 27 , 28 , 50 , 68 , 82 ]. Indeed, the findings of the current study show that mothers are more likely to vaccinate boys than girls.…”
Section: Discussionsupporting
confidence: 91%
“…There is some evidence that SLIV programs can produce community-wide indirect effects among preschool-aged children and adults; however, studies have produced conflicting results [20,21,[31][32][33]. Many prior SLIV evaluations used study designs that are subject to confounding [17,18,20,21,[26][27][28][31][32][33]; those that have used more rigorous designs did not measure health outcomes [23][24][25]34,35] or enrolled small numbers of schools [16,19]. To our knowledge, no prior studies have rigorously measured the impacts of large-scale SLIV interventions on student and community-wide health outcomes over multiple years.…”
Section: Plos Medicinementioning
confidence: 99%
“…In terms of knowledge, there was no significant difference between the comparison of 2021 and 2019 (p=0.134). However, on average, only a quarter of the students knew the incubation period time of influenza, and one similar study found that university education has a positive impact on influenza knowledge, 16 indicating that students at this university do not pay much Open attention to influenza-related courses. The questions 'wearing a mask can prevent the spread of influenza to some 'influenza can be spread through close contact with patients' and 'compared with developing immunity from influenza infection, getting immunity from influenza vaccination has better cost-effectiveness' are answered significantly more correctly in 2021 than in 2019.…”
Section: Discussionmentioning
confidence: 99%